Developmental programs of human erythroleukemia cells: globin gene expression and methylation. - Enver, T (1988)
We investigated the programs of globin gene expression in three known (K562, HEL, and KMOE) and three novel (OCI-M1, OCI-M2, and HEL-R) human erythroleukemic cell lines of adult origin. RNAs from induced and uninduced cells were analyzed for epsilon-, gamma-, delta-, and beta-, zeta-globin-specific transcripts. While high-level gamma-globin expression was common, the lines differed in their expression of embryonic (epsilon, zeta) and adult (delta, beta) globin mRNAs. The patterns of globin gene methylation were generally consistent with their observed expression profiles, with many of the same correlations being seen in normal cells. Although the programs of globin gene expression and methylation displayed by the lines appeared to be diverse, they were not random; rather, they made developmental sense, mimicking defined globin gene programs observed during normal human development. The characteristics exhibited by several of these lines suggest that they may have been derived from the transformation of multi- or oligopotent hematopoietic progenitor cells. We speculate that the expression of fetal or embryonic globins in these adult erythroleukemic cell lines is not an aberration of neoplastic transformation but is indicative of a fetal or embryonic potential in normal adult hematopoietic progenitors.